2019
DOI: 10.1111/jdi.13167
|View full text |Cite
|
Sign up to set email alerts
|

Standard medical nutrition therapy of 25 kcal/kg ideal bodyweight/day often does not reach even resting energy expenditure for patients with type 2 diabetes

Abstract: Aims/Introduction: In Japan, an ideal bodyweight (IBW) calculated by 22 9 height (m) 2 has commonly been used in the planning of medical nutrition therapy (MNT). However, there have been concerns regarding calorie deficits in fulfilling resting energy expenditure (REE) for patients with type 2 diabetes undergoing MNT as defined by 25 kcal/kg IBW/day. The objective of the present study was to measure REE in patients with type 2 diabetes and verify the validity of MNT with 25 kcal/kg IBW/day. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The nutritional consensus statements advocate for an energy intake of 25-35 kcal/kg/d for patients with CKD [ 29 ]. Despite this, a multitude of studies have showed that the energy intake of patients with CKD [ 30 ] and T2DM [ 31 ] are seriously insufficient. However, individually characterizing energy intake for each patient can be a huge challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional consensus statements advocate for an energy intake of 25-35 kcal/kg/d for patients with CKD [ 29 ]. Despite this, a multitude of studies have showed that the energy intake of patients with CKD [ 30 ] and T2DM [ 31 ] are seriously insufficient. However, individually characterizing energy intake for each patient can be a huge challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the target energy intake for critically ill patients has been recommended as 25–30 kcal/kg/day [ 84 ]. However, the formula used for this estimation was developed based on energy expenditure outside the acute phase [ 85 , 86 ], and whether this is truly optimal for critically ill conditions remains unclear. Moreover, opinions vary depending on the timing, particularly in the early acute phase (the first 2–3 days after ICU admission) when it overlaps with the peak of invasiveness and inflammation, necessitating cautious nutrition delivery [ 87 ].…”
Section: Introductionmentioning
confidence: 99%